In this paper, the infinite sums of reciprocals and the partial sums derived from Chebyshev polynomials are studied. For the infinite sums of reciprocals, we apply the floor function to the reciprocals of these sums to obtain some new and interesting identities involving the Chebyshev polynomials. Simultaneously, we get several identities about the partial sums of Chebyshev polynomials by the relation of two types of Chebyshev polynomials.
Citation: Fan Yang, Yang Li. The infinite sums of reciprocals and the partial sums of Chebyshev polynomials[J]. AIMS Mathematics, 2022, 7(1): 334-348. doi: 10.3934/math.2022023
[1] | Jiankang Wang, Zhefeng Xu, Minmin Jia . Distribution of values of Hardy sums over Chebyshev polynomials. AIMS Mathematics, 2024, 9(2): 3788-3797. doi: 10.3934/math.2024186 |
[2] | Zhenjiang Pan, Zhengang Wu . The inverses of tails of the generalized Riemann zeta function within the range of integers. AIMS Mathematics, 2023, 8(12): 28558-28568. doi: 10.3934/math.20231461 |
[3] | Taekyun Kim, Dae San Kim, Dmitry V. Dolgy, Jongkyum Kwon . Sums of finite products of Chebyshev polynomials of two different types. AIMS Mathematics, 2021, 6(11): 12528-12542. doi: 10.3934/math.2021722 |
[4] | Utkal Keshari Dutta, Prasanta Kumar Ray . On the finite reciprocal sums of Fibonacci and Lucas polynomials. AIMS Mathematics, 2019, 4(6): 1569-1581. doi: 10.3934/math.2019.6.1569 |
[5] | S. Akansha, Aditya Subramaniam . Exploring Chebyshev polynomial approximations: Error estimates for functions of bounded variation. AIMS Mathematics, 2025, 10(4): 8688-8706. doi: 10.3934/math.2025398 |
[6] | Jin Li . Barycentric rational collocation method for semi-infinite domain problems. AIMS Mathematics, 2023, 8(4): 8756-8771. doi: 10.3934/math.2023439 |
[7] | Muhammad Uzair Awan, Nousheen Akhtar, Artion Kashuri, Muhammad Aslam Noor, Yu-Ming Chu . 2D approximately reciprocal ρ-convex functions and associated integral inequalities. AIMS Mathematics, 2020, 5(5): 4662-4680. doi: 10.3934/math.2020299 |
[8] | Tingting Du, Zhengang Wu . Some identities involving the bi-periodic Fibonacci and Lucas polynomials. AIMS Mathematics, 2023, 8(3): 5838-5846. doi: 10.3934/math.2023294 |
[9] | Xiao Jiang, Shaofang Hong . On the denseness of certain reciprocal power sums. AIMS Mathematics, 2019, 4(3): 412-419. doi: 10.3934/math.2019.3.412 |
[10] | Waleed Mohamed Abd-Elhameed, Omar Mazen Alqubori, Ahmed Gamal Atta . A collocation procedure for the numerical treatment of FitzHugh–Nagumo equation using a kind of Chebyshev polynomials. AIMS Mathematics, 2025, 10(1): 1201-1223. doi: 10.3934/math.2025057 |
In this paper, the infinite sums of reciprocals and the partial sums derived from Chebyshev polynomials are studied. For the infinite sums of reciprocals, we apply the floor function to the reciprocals of these sums to obtain some new and interesting identities involving the Chebyshev polynomials. Simultaneously, we get several identities about the partial sums of Chebyshev polynomials by the relation of two types of Chebyshev polynomials.
The properties of orthogonal polynomials and recursive sequences are popular in number theory. They are important in theoretical research and application. The famous Chebyshev polynomials and Fibonacci polynomials are widely used in the field of function, approximation theory and difference equation. They also promote the development of both the branch of mathematics such as cryptography, combinatorics and application of discipline such as intelligent sensing, satellite positioning. Furthermore, they are close to the Fibonacci numbers and Lucas numbers. Therefore, a large number of scholars have investigated them and get many properties and identities.
In the aspect of sums of reciprocals, Millin [1] originally studied the infinite sums of reciprocal Fibonacci series where the subscript is 2n. Based on the initial achievement, Good [2] further studied this issue and proved
∞∑n=01F2n=7−√52. |
Afterwards, Ohtsuka and Nakamura [3] deduced the infinite sum of reciprocal Fibonacci series
⌊(∞∑k=n1Fk)−1⌋={Fn−Fn−1,if n is even and n≥2 ,Fn−Fn−1−1,if n is odd and n≥1; |
and the infinite sum of reciprocal square Fibonacci series
⌊(∞∑k=n1F2k)−1⌋={FnFn−1−1,if n is even and n≥2 ,FnFn−1,if n is odd and n≥1; |
Similar properties were investigated in several different ways, see reference [4,5]. Falcón and Plaza [6,7,8] used Fibonacci polynomials to study Fibonacci numbers and get a lot of identities. For example,
n−1∑k=1Fk(x)Fn−k(x)=(n−1)xFn(x)+2nFn−1(x)x2+4, |
n∑k=1Fk(x)=Fn+1(x)+Fn(x)−1x |
where n and k are positive integers. This fact allows them to invest some integer sequences in a new and direct way. With these fundamental achievements, Wu and Zhang[9] proceeded generation and deduced the the infinite sum of reciprocal Fibonacci polynomials
⌊(∞∑k=n1Fk(x))−1⌋={Fn(x)−Fn−1(x),if n is even and n≥2 ,Fn(x)−Fn−1(x)−1,if n is odd and n≥1; |
and the the infinite sum of reciprocal square Fibonacci polynomials
⌊(∞∑k=n1F2k(x))−1⌋={xFn(x)Fn−1(x)−1,if n is even and n≥2 ,xFn(x)Fn−1(x),if n is odd and n≥1; |
where x is any positive integer. besides, Panda et al.[10] did some research about bounds for reciprocal sums in terms of balancing and Lucas-balancing sequences. Also, Dutta and Ray[11] found some identities about finite reciprocal sums of Fibonacci and Lucas polynomials.
As we know, the first and the second kind of Chebyshev polynomials are usually defined as follows: Tn+2(x)=2xTn+1(x)−Tn(x), n≥0, with the initial values T0(x)=1, T1(x)=x; Un+2(x)=2xUn+1(x)−Un(x), n≥0, with the initial values U0(x)=1, U1(x)=2x; Then from the second-order linear recurrence sequences we have
Tn(x)=12[(x+√x2−1)n+(x−√x2−1)n],Un(x)=12√x2−1[(x+√x2−1)n+1−(x−√x2−1)n+1]. |
Based on these sequences, many scholars used these polynomials to study the Fibonacci sequences and the Lucas sequences and have investigated them and got many properties of Fn and Ln. For example, Zhang[12] used the Chebyshev polynomials and has obtain the general formulas involving Fn and Ln
∑a1+a2+⋯+ak+1=nFm(a1+1)⋅Fm(a2+1)⋯Fm(ak+1+1)=(−i)mnFk+1m2k⋅k!U(k)n+k(imLm2). |
∑a1+a2+…+ak+1=n+k+1Lm(a1+1)⋅Lm(a2+1)⋯Lm(ak+1+1) |
=(−i)m(n+k+1)2k!k+1∑h=0(im+2Lm2)h(k+1)!h!(k+1−h)!U(k)n+2k+1−h(imLm2), |
where k, m are any positive integers, a1, a2, ⋯ak+1 are nonnegative integers and i is the square root of −1. Wu and Yang[13] also studied Chebyshev polynomials and got a lot of properties. Besides, Dilcher and Stolarsky[14] established several related results involving resultants and discriminants about Chebyshev polynomials. Furthermore, bounds about the discriminant of the Chebyshev polynomials were given by Filipovski[15].
A variety of sums about Chebyshev polynomials are hot issues in the number theory all the time. For example, Cesarano [16] gained several conclusions about the generating function of Chebyshev polynomials
∞∑n=0ξnTn+l(x)=(1−ξx)Tl(x)−ξ(1−x2)Ul−11−2ξx+ξ2 |
and the identical equation
∞∑n=0ξnUn−1+l(x)=ξTl(x)−(1−ξx)Ul−11−2ξx+ξ2 |
In this, ξ is a real number and −1<ξ<1. Furthermore, Knopfmacher et al.[17] did some research and got the result as follows:
1Um(x)=1m+1m∑j=1(−1)j+1sin2θjx−cosθj |
and the identical equation
1+Um−1(x)Um(x)=1m+1m∑j=1[1+(−1)j+1]sin2θjx−cosθj, |
where θj=jπm+1, m is a positive integer.
In this paper, we combine Ohtsuka and Falcón's ideas. Then we consider the subseries of infinite sums derived from the reciprocals of the Chebyshev polynomials and prove the following:
Theorem 1. For any positive integer n, m and x, we have the following formula
⌊(∞∑k=n1Tmk(x))−1⌋=Tmn(x)−Tmn−m(x) |
Theorem 2. For any positive integer n, and x, we have the following formula
⌊(∞∑k=n1Uk(x))−1⌋=Un(x)−Un−1(x)−1. |
Theorem 3. For any positive integer n, and x, we have the following formula
⌊(∞∑k=n1U2k(x))−1⌋=U2n(x)−U2n−1(x)−1. |
With Falcón's enlightening, we can apply similar method into deduction of partial sums of Chebyshev polynomials. For convenient expression, we firstly set
Gn(x)=Un−1(x)Un(x)+Un−1(x)Un+1(x) |
Mn(x)=Un−2(x)Un(x)+Un−1(x)Un(x) |
and obtain:
Theorem 4. For any positive integer n,
2n+1∑k=0k2Uk(x)=12(2n+1)U′2n+1(x)−G′n(x)+1+(n+1)U′2n+2(x)+Mn(x). |
Theorem 5. For any positive integer n,
2n∑k=0k2Tk(x)=12(2n+1)2U2n−1(x)−U′2n(x)+2(n+1)2U2n+2(x)−U′2n+1(x). |
Theorem 6. For any positive integer n,
2n∑k=0k3Tk(x)=4(n+1)3U2n+2(x)+12(2n+1)3U2n+1(x)−Gn(x)−(3n+32)U′2n−1(x)−3nU′2n(x)+3M′n(x)−1. |
In order to prove the results of the infinite sums of reciprocal Chebyshev polynomials, several lemmas are needed.
Let α=x+√x2−1 and β=x−√x2−1, then we have the following lemmas.
Lemma 1. For any positive integer n, we have
U2n(x)=1+Un−1(x)Un+1(x), |
U2n(x)=4x2+Un−2(x)Un+2(x). |
Proof. From the definition of Chebyshev polynomials, we have
U2n(x)−Un−1(x)Un+1(x)=(αn+1−βn+1)2−(αn−βn)(αn+2−βn+2)(α−β)2=α2n+2+β2n+2+α2+β2−2−α2n+2−β2n+2(α−β)2=1.U2n(x)−Un−2(x)Un+2(x)=(αn+1−βn+1)2−(αn−1−βn−1)(αn+3−βn+3)(α−β)2=α2n+2+β2n+2+α4+β4−2−α2n+2−β2n+2(α−β)2=(α+β)2=4x2. |
Lemma 2. For any positive integer n, we have
T2n(x)=Tn−1(x)Tn+1(x)+1−x2, |
T2n(x)=Tn−2(x)Tn+2(x)+4x2(1−x2). |
Proof. From the definition of Chebyshev polynomials, we have
T2n(x)−Tn−1(x)Tn+1(x)=14[(αn+βn)2−(αn−1+βn−1)(αn+1+βn+1)]=−14[α2+β2−2]=−14(α−β)2=1−x2.T2n(x)−Tn−2(x)Tn+2(x)=14[(αn+βn)2−(αn−2+βn−2)(αn+2+βn+2)]=14[α2n+β2n−α4−β4+2−α2n−β2n]=−14(α+β)2(α−β)2=4x2(1−x2). |
Lemma 3. For any positive integer n and m, we have
Tn(Tm(x))=Tnm(x), |
Un(Tm(x))=Um(n+1)−1(x)Um−1(x). |
Proof. See Reference [12].
Lemma 4. For any positive integer n and x, we have
1Tn(x)+1Tn+1(x)<1Tn(x)−Tn−1(x)−1Tn+2(x)−Tn+1(x),1Tn(x)+1Tn+1(x)>1Tn(x)−Tn−1(x)+1−1Tn+2(x)−Tn+1(x)+1. |
Proof. The first inequality equivalent to
Tn(x)+Tn+1(x)Tn(x)Tn+1(x)<Tn+2(x)−Tn+1(x)−Tn(x)+Tn−1(x)(Tn(x)−Tn−1(x))(Tn+2(x)−Tn+1(x)), | (2.1) |
or
[Tn(x)+Tn+1(x)](Tn(x)−Tn−1(x)+1)(Tn+2(x)−Tn+1(x)+1)<Tn(x)Tn+1(x)[Tn+2(x)−Tn+1(x)−Tn(x)+Tn−1(x)], |
Then we have
T2n(x)Tn+2(x)+T2n+1(x)Tn−1(x)<Tn−1(x)Tn+2(x)Tn(x)+Tn−1(x)Tn+2(x)Tn+1(x), |
applying Lemma 2, inequality (2.1) is equivalent to
(1−x2)[Tn−1(x)+Tn+2(x)]<0. | (2.2) |
For any positive x and n≥1, 1−x2<0 and Tn−1(x)+Tn+2(x)>0. Thus it is very easy to check inequality (2.2) is true. Similarly, we can consider the second inequality of Lemma 4. The second inequality is equivalent to
Tn(x)+Tn+1(x)Tn(x)Tn+1(x)>Tn+2(x)−Tn+1(x)−Tn(x)+Tn−1(x)(Tn(x)−Tn−1(x)+1)(Tn+2(x)−Tn+1(x)+1), | (2.3) |
or
T2n(x)Tn+2(x)−Tn−1(x)Tn(x)Tn+2(x)−Tn−1(x)Tn+1(x)Tn+2(x)+Tn(x)Tn+2(x)+Tn+1(x)Tn+2(x)+T2n+1(x)Tn−1(x)−T2n+1(x)+T2n(x)−Tn(x)Tn−1(x)−Tn+1(x)Tn−1(x)+Tn(x)+Tn+1(x)>0, |
applying Lemma 2, inequality (2.3) is equivalent to
(Tn+1(x)−(x2−1))Tn+2(x)−(Tn(x)+(x2−1))Tn−1(x)+Tn(x)+Tn+1(x)>0. | (2.4) |
For any positive x and n≥1,
(Tn+1(x)−(x2−1))Tn+2(x)−(Tn(x)+(x2−1))Tn−1(x)>0 |
Thus it is very easy to check inequality (2.4) is true.
Lemma 5. For any positive integer n and x,
1Un(x)+1Un+1(x)>1Un(x)−Un−1(x)−1Un+2(x)−Un+1(x),1Un(x)+1Un+1(x)<1Un(x)−Un−1(x)−1−1Un+2(x)−Un+1(x)−1. |
Prove. The first inequality is equivalent to
Un+1(x)+Un(x)Un+1(x)Un(x)>Un+2(x)−Un+1(x)−Un(x)+Un−1(x)(Un(x)−Un−1(x))(Un+2(x)−Un+1(x)), | (2.5) |
or
[Un+1(x)+Un(x)](Un(x)−Un−1(x))(Un+2(x)−Un+1(x))>Un+1(x)Un(x)[Un+2(x)−Un+1(x)−Un(x)+Un−1(x)], |
Then we have
U2n(x)Un+2(x)+U2n+1(x)Un−1(x)>Un(x)Un+2(x)Un−1(x)+Un−1(x)Un+1(x)Un+2(x), |
applying Lemma 1, inequality (2.5) is equivalent to
Un+2(x)+Un−1(x)>0. | (2.6) |
For any positive x and n≥1, it is very easy to check inequality (2.6) is true. Similarly, we can consider the second inequality of Lemma 5.
Un+1(x)+Un(x)Un+1(x)Un(x)<Un+2(x)−Un+1(x)−Un(x)+Un−1(x)(Un(x)−Un−1(x)−1)(Un+2(x)−Un+1(x)−1), | (2.7) |
or
U2n(x)Un+2(x)−Un−1(x)Un(x)Un+2(x)−Un−1(x)Un+1(x)Un+2(x)−Un(x)Un+2(x)−Un+1(x)Un+2(x)+U2n+1(x)Un−1(x)+U2n+1(x)−U2n(x)+Un(x)Un−1(x)+Un+1(x)Un−1(x)+Un(x)+Un+1(x)<0, |
applying Lemma 1, inequality (2.7) equivalent to
Un+2(x)+Un−1(x)+Un(x)Un−1(x)+Un(x)+Un+1(x)<Un+1(x)Un+2(x). | (2.8) |
For any positive x and n≥1, it is very easy to check inequality (2.8) is true.
Lemma 6. For any positive integers n and x, we have
1U2n(x)+1U2n+1(x)>1U2n(x)−U2n−1(x)−1U2n+2(x)−U2n+1(x),1U2n(x)+1U2n+1(x)<1U2n(x)−U2n−1(x)−1−1U2n+2(x)−U2n+1(x)−1. |
Proof. The first inequality is equivalent to
U2n(x)+U2n+1(x)U2n(x)U2n+1(x)>U2n+2(x)−U2n+1(x)−U2n(x)+U2n−1(x)(U2n+2(x)−U2n+1(x))(U2n(x)−U2n−1(x)), | (2.9) |
or
[U2n(x)+U2n+1(x)](U2n+2(x)−U2n+1(x))(U2n(x)−U2n−1(x))>U2n(x)U2n+1(x)[U2n+2(x)−U2n+1(x)−U2n(x)+U2n−1(x)], |
Then we have
U4n(x)U2n+2(x)−U2n(x)U2n+2(x)U2n−1(x)−U2n+1(x)U2n+2(x)U2n−1(x)+U4n+1(x)U2n−1(x)>0, |
applying Lemma 1, inequality (2.9) is equivalent to
U2n+2(x)+2Un−1(x)Un+1(x)U2n+2(x)+U2n−1(x)+2Un(x)Un+2(x)U2n−1(x)>0. | (2.10) |
For any positive x and n≥1, it is very easy to check inequality (2.10) is true. Similarly, we can consider the second inequality of Lemma 6. The second inequality is equivalent to
U2n(x)+U2n+1(x)U2n(x)U2n+1(x)<U2n+2(x)−U2n+1(x)−U2n(x)+U2n−1(x)(U2n+2(x)−U2n+1(x)−1)(U2n(x)−U2n−1(x)−1), | (2.11) |
or
U4n(x)U2n+2(x)−U4n(x)−U2n(x)U2n+2(x)U2n−1(x)−U2n+1(x)U2n+2(x)U2n−1(x)+U4n+1(x)U2n−1(x)+U2n(x)U2n−1(x)+U2n+1(x)U2n−1(x)−U2n(x)U2n+2(x)−U2n+1(x)U2n+2(x)+U4n+1(x)+U2n(x)+U2n+1(x)<0, |
applying Lemma 1, inequality (2.11) is equivalent to
U2n(x)U2n−1(x)+U2n(x)+U2n+1(x)+U2n+2(x)+2Un−1(x)Un+1(x)U2n+2(x)+U2n−1(x) |
2Un(x)Un+2(x)U2n−1(x)+2Un(x)Un+2(x)<U2n+1(x)U2n+2(x)+2Un−1(x)Un+1(x). | (2.12) |
For any positive x and n≥1, it is very easy to check inequality (2.12) is true.
Aiming to prove the results of the partial sums of Chebyshev polynomials, the lemmas below are necessary.
Lemma 7. For any positive integer n≥2
Tn(x)=12Un(x)−12Un−2(x)n∑k=1Tk(x)=12Un(x)+12Un−1(x)−12 |
Prove. The general term formula of Chebyshev polynomials is as follows
Tn(x)=12[(x+√x2−1)n+(x−√x2−1)n]Un(x)=12√x2−1[(x+√x2−1)n+1−(x−√x2−1)n+1] |
For convenient proving, we set α=x+√x2−1, β=x−√x2−1, and easily verify α+β=2x, αβ=1. Thus, according to the definition we get
12Un(x)−12Un−2(x)=12(αn+1−βn+1α−β−αn−1−βn−1α−β)=12(α−β)[αn−1(α2−1)−βn−1(β2−1)]=12(α−β)[αn−1(α2−αβ)−βn−1(β2−αβ)]=12(α−β)[αn(α−β)+βn(α−β)]=12(αn+βn). |
This proves the first equation. And next we prove the second equation
n∑k=1Tk(x)=12n∑k=2Uk(x)−12n∑k=2Uk−2(x)+T1(x)=12n∑k=2Uk(x)−12n−2∑k=0Uk(x)+T1(x)=12Un(x)+12Un−1(x)−T1(x)−12+T1(x)=12Un(x)+12Un−1(x)−12. |
This proves Lemma 7.
Lemma 8. For any positive integer n
2n∑k=1Uk(x)=Un−1(x)Un(x)+Un−1(x)Un+1(x), | (2.13) |
2n−1∑k=1Uk(x)=Un−2(x)Un(x)+Un−1(x)Un(x). | (2.14) |
Prove. In accordance of the general term formula of Chebyshev polynomials, it is not hard to get
U2n+1(x)=Un(x)Un+1(x)−Un(x)Un−1(x),U2n+2(x)=U2n+1(x)−Un+1(x)Un−1(x)−1,U2n+1(x)=Un+2(x)Un(x)+1. |
Easily test that when n=1, identical Eq (2.13) is right. Supposing that n=m, Eq (2.13) is right. Then when n=m+1,
2m+2∑k=1Uk(x)=Um−1(x)Um+1(x)+Um−1(x)Um(x)+U2m+1(x)+U2m+2(x)=Um+1(x)Um(x)+U2m+1−1=Um(x)Um+2(x)+Um+1(x)Um(x). |
Applying mathematical induction, it is not hard to prove identical Eq (2.14). This proves Lemma 8.
Lemma 9. For any positive integers n,
2n∑k=0kTk(x)=12(2n+1)U2n−1(x)+(n+1)U2n(x)−Gn(x)2n∑k=0kUk(x)=12U′n+1(x)+12U′n(x)−Gn(x) |
Prove. According to Lemma 7, we have
n+1∑k=0Tk(x)=Un+1(x)+Un(x)+12. |
Through derivation on the left and right sides, we get
n∑k=0(k+1)Uk(x)=U′n+1(x)+U′n(x)2. |
Applying Lemma 7 and Lemma 8, we obtain
2n∑k=1kUk(x)=12U′2n+1(x)+12U′2n(x)−2n∑k=1Uk(x)=12U′2n+1(x)+12U′2n(x)−Gn(x)2n∑k=1kTk(x)=x+122n∑k=2kUk(x)−122n∑k=2kUk−2(x)=x+122n∑k=2kUk(x)−122n−2∑k=0(k+2)Uk(x)=(n+12)U2n−1(x)+(n+1)U2n(x)−2n∑k=1Uk(x)=(n+12)U2n−1(x)+(n+1)U2n(x)−Gn(x). |
This proves Lemma 9.
In this section, we will prove our theorems. For the infinite sums of reciprocal Chebyshev polynomials, firstly we prove Theorem 1. For any positive integer n and x, using Lemma 4, we have
∞∑k=n1Tk(x)=∞∑k=s(1T2k−1(x)+1T2k(x))<∞∑k=s(1T2k−1(x)−T2k−2(x)−1T2k+1(x)−T2k(x))=1Tn(x)−Tn−1(x) |
In the similar way, we have
∞∑k=n1Tk(x)=∞∑k=s(1T2k−1(x)+1T2k(x))>∞∑k=s(1T2k−1(x)−T2k−2(x)+1−1T2k+1(x)−T2k(x)+1)=1Tn(x)−Tn−1(x)+1. |
And then we have
⌊(∞∑k=n1Tk(x))−1⌋=Tn(x)−Tn−1(x) |
and then let x=Tm(x), according to Lemma 3, we can get
⌊(∞∑k=n1Tmk(x))−1⌋=Tmn(x)−Tmn−m(x) |
This proved Theorem 1.
Next, Theorem 2 will be proved. For any positive integer n and x, using Lemma 5, we have
∞∑k=n1Uk(x)=∞∑k=s(1U2k−1(x)+1U2k(x))<∞∑k=s(1U2k−1(x)−U2k−2(x)−1−1U2k+1(x)−U2k(x)−1)=1Un(x)−Un−1(x)−1. |
In the similar way, we have
∞∑k=n1Uk(x)=∞∑k=s(1U2k−1(x)+1U2k(x))>∞∑k=s(1U2k−1(x)−U2k−2(x)−1U2k+1(x)−U2k(x))=1Un(x)−Un−1(x). |
And then we have
Un(x)−Un−1(x)−1<(∞∑k=n1Uk(x))−1<Un(x)−Un−1(x). |
that is
⌊(∞∑k=n1Uk(x))−1⌋=Un(x)−Un−1(x)−1. |
This proved Theorem 2.
Then we shall prove Theorem 3. Using Lemma 6, we can get
∞∑k=n1U2k(x)=∞∑k=s(1U22k−1(x)+1U22k(x))<∞∑k=s(1U22k−1(x)−U22k−2(x)−1−1U22k+1(x)−U22k(x)−1)=1U2n(x)−U2n−1(x)−1. |
In the similar way, we have
∞∑k=n1U2k(x)=∞∑k=s(1U22k−1(x)+1U22k(x))>∞∑k=s(1U22k−1(x)−U22k−2(x)−1U22k+1(x)−U22k(x))=1U2n(x)−U2n−1(x) |
and then we can get
⌊(∞∑k=n1U2k(x))−1⌋=U2n(x)−U2n−1(x)−1. |
This proved Theorem 3.
For the partial sums of Chebyshev polynomials, firstly we shall prove Theorem 4. According to Lemma 9, we have
2n+2∑k=0kTk(x)=12(2n+3)U2n+1(x)+(n+2)U2n+2(x)−Gn+1(x) |
Through simultaneous derivation on the left and right sides, we deduce
2n+1∑k=1k2Uk−1(x)=12(2n+3)U′2n+1(x)+(n+2)U′2n+2(x)−G′n(x). |
According to Lemma 8 and Lemma 9 we get
2n+1∑k=0k2Uk(x)=2n+2∑k=1k2Uk−1(x)−22n+1∑k=1kUk(x)−2n+1∑k=0Uk(x)=2n+2∑k=1k2Uk−1(x)−22n+1∑k=1(k+1)Uk(x)+2n+1∑k=0Uk(x)=(n+12)U′2n+1(x)+(n+1)U′2n+2(x)−G′n(x)+Mn(x)+1. |
Applying Lemma 7 and Lemma 8, we get
2n∑k=0k2Tk(x)=x+122n∑k=2k2Uk(x)−122n∑k=2k2Uk−2(x)=x+122n∑k=2k2Uk(x)−122n−2∑k=0(k+2)2Uk(x). |
Simplify the above, we have
2n∑k=0k2Tk(x)=12(2n+1)2U2n−1(x)+2(n+1)2U2n+2(x)−U′2n+1(x)−U′2n(x) |
This proved Theorem 4 and Theorem 5.
Theorem 6 shall be proved below. According to Lemma 7 and Lemma 8, we have
2n∑k=0k3Tk(x)=x+122n∑k=2k3Uk(x)−122n∑k=2k3Uk−2(x)=x+122n∑k=2k3Uk(x)−122n−2∑k=0(k+2)3Uk(x)=−2n−2∑k=2(3k2+6k+4)Uk(x)+12(2n+1)3Un(x)+4(n+1)3U2n+2(x)−26x−4=4(n+1)3U2n+2(x)+12(2n+1)3U2n+1(x)−Gn(x)−(3n+32)U′2n−1(x)−3nU′2n(x)+3M′n(x)−1. |
This proved Theorem 6.
In this paper, the infinite sums of reciprocals and the partial sums derived from Chebyshev polynomials are studied. For the infinite sums of reciprocals, we apply the floor function to the reciprocals of these sums to obtain Theorem 1, Theorem 2 and Theorem 3 involving the Chebyshev polynomials. Simultaneously, we get Theorem 4, Theorem 5 and Theorem 6 about the partial sums of Chebyshev polynomials by the relation of two types of Chebyshev polynomials. Our results can enrich the related research domain with respect to orthogonal polynomials and recursive sequences. Besides, the results are hoped to be applied into other branches of mathematics or other disciplines out of mathematics.
The authors would like to thank Xi'an Shiyou University for the support of this research.
The authors declare there is no conflicts of interest in this paper.
[1] | D. A. Millin, Problem H-237, Fibonacci Quart., 12 (1974), 309. |
[2] | I. J. Good, A reciprocal series of Fibonacci numbers, Fibonacci Quart., 12 (1974), 346. |
[3] | H. Ohtsuka, S. Nakamura, On the sum of the reciprocal of Fibonacci numbers, Fibonacci Quart., 46 (2009), 153–159. |
[4] |
W. Zhang, T. Wang, The infinite sum of the reciprocal of Pell numbers, Appl. Math. Comput., 218 (2012), 6164–6167. doi: 10.1016/j.amc.2011.11.090. doi: 10.1016/j.amc.2011.11.090
![]() |
[5] |
G. Zhang, The infinite sum of reciprocal of the Fibonacci numbers, J. Math. Res. Expo., 31 (2011), 1030–1034. doi: 10.3770/j.issn:1000-341X.2011.06.010. doi: 10.3770/j.issn:1000-341X.2011.06.010
![]() |
[6] |
S. Falcón, Á. Plaza, On k-Fibonacci sequences and polynomials and their derivatives, Chaos Solution. Fract., 39 (2009), 1005–1019. doi: 10.1016/j.chaos.2007.03.007. doi: 10.1016/j.chaos.2007.03.007
![]() |
[7] |
S. Falcón, Á. Plaza, The k-Fibonacci sequences and the Pascal 2-triangle, Chaos Solution. Fract., 38 (2007), 38–49. doi: 10.1016/j.chaos.2006.10.022. doi: 10.1016/j.chaos.2006.10.022
![]() |
[8] |
S. Falcón, Á. Plaza, The k-Fibonacci hyperbolic functions, Chaos Solution. Fract., 38 (2008), 409–420. doi: 10.1016/j.chaos.2006.11.019. doi: 10.1016/j.chaos.2006.11.019
![]() |
[9] | Z. Wu, W. Zhang, The sums of the reciprocal of Fibonacci polynomials and Lucas polynomials, J. Inequal. Appl., 134 (2012). doi: 10.1186/1029-242X-2012-134. |
[10] | G. K. Panda, T. Komatsu, R. K. Davala, Reciprocal sums of sequences involving balancing and lucas-balancing numbers, Math. Rep., 20 (2018), 201–214. |
[11] |
U. K. Dutta, P. K. Ray, On the finite reciprocal sums of fibonacci and lucas polynomials, AIMS Math., 4 (2019), 1569–1581. doi: 10.3934/math.2019.6.1569. doi: 10.3934/math.2019.6.1569
![]() |
[12] | W. Zhang, Some identities involving the Fibonacci numbers and Lucas numbers, Fibonacci Quart., 42 (2004), 149–154. |
[13] | X. Wu, G. Yang, The general formula of Chebyshev polynomials, J. Wuhan Trans. U., 24 (2000), 573–576. |
[14] |
K. Dilcher, K. Stolarsky, Resultants and discriminants of chebyshev and related polynomials, T. Am. Math. Soc., 357 (2005), 965–981. doi: 10.1090/S0002-9947-04-03687-6. doi: 10.1090/S0002-9947-04-03687-6
![]() |
[15] | S. Filipovski, A lower bound for the discriminant of polynomials related to Chebyshev polynomials, Discrete Math., 344 (2021). doi: 10.1016/j.disc.2020.112235. |
[16] | C. Cesarano, Identities and generating functions on Chebyshev polynomials, Georgian Math. J., 19 (2012), 427–440. doi; 10.1515/gmj-2012-0031. |
[17] | A. Knopfmacher, T. Mansour, A. O. Munagi, Staircase words and Chebyshev polynomials, Appl. Anal. discr. Math., 4 (2010), 81–95. |